2022
DOI: 10.1093/inthealth/ihac046
|View full text |Cite
|
Sign up to set email alerts
|

Related factors to the coping style of patients with sudden sensorineural hearing loss

Abstract: Background Coping style can affect the patient's physical and mental health management. Therefore this study aimed to identify factors related to the coping style of young and middle-aged sudden sensorineural hearing loss (SSNHL) patients to provide reference for clinical nursing practice. Methods A cross-sectional study was conducted on young and middle-aged SSNHL patients hospitalized in the otolaryngology departments of fo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 30 publications
0
2
0
Order By: Relevance
“…Women's psychological endurance is weak, and women are more inclined to adopt negative coping styles such as avoidance and surrender. 48 In addition, sex hormones can also explain the biological differences in symptom burden. 49 The findings of a longitudinal study revealed a significant improvement in sleep deprivation among male patients compared to their female counterparts 12 months after KT.…”
Section: Discussionmentioning
confidence: 99%
“…Women's psychological endurance is weak, and women are more inclined to adopt negative coping styles such as avoidance and surrender. 48 In addition, sex hormones can also explain the biological differences in symptom burden. 49 The findings of a longitudinal study revealed a significant improvement in sleep deprivation among male patients compared to their female counterparts 12 months after KT.…”
Section: Discussionmentioning
confidence: 99%
“…The following coping strategies are less adequate: "Confrontative Coping", "Seeking Social Support", and, especially, "Distancing and Escape/Avoidance" [24]. Previously, it was shown that maladaptive coping strategies prevail in people with personality type D, both in healthy individuals [24] and in people with various diseases [25], particularly in CAD patients [8,26,27]. Moreover, a recent study showed that inadequate coping strategies mediate the adverse effects of personality type D on the prognoses of CAD patients after a PCI [8].…”
Section: Introductionmentioning
confidence: 99%